ANALYSIS OF PRAGMATIC POLITENESS STRATEGIES IN FRANZ KAFKA’S NOVEL THE METAMORPHOSIS - Muhammad Saddam; Yasmin Elfa Mediena; Aidil Syah Putra (Media Inovasi Pendidikan dan Publikasi, 2024)
This study explores the pragmatic politeness strategies employed in Franz Kafka’s novel